RACIAL DISCRIMINATION ISSUES AS SHOWN BY SOLOMON AND PATSEY IN 12 YEARS A SLAVE MOVIE - Julan, Dezelin Brigitha; Surya, Satyawati; Valiantien, Nita Maya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2021)
This study aimed to describe the portrayal of racial discrimination as shown in Solomon and Patsey characters of 12 Years A Slave movie. In order to do so, this study used Allport’s theory of intentional, explicit discrimination focusing on several types of racial discrimination such as verbal antagonism, avoidance, segregation, physical attacks, and extermination. The data used in this study were words in forms of narration, dialogue, and action related to the portrayal of racial discrimination towards Solomon and Patsey characters that were taken from 12 Years A Slave movie script. This study showed that the portrayal of racial discrimination as shown in Solomon and Patsey characters of 12 Years A Slave movie was classified into five types of intentional, explicit discrimination behaviours such as verbal antagonism, avoidance, segregation, physical attacks, and extermination. On one hand, the portrayal of racial discrimination as shown in Solomon character was included as verbal antagonism, avoidance, segregation, physical attacks, and extermination. On the other hand, the portrayal as shown in Patsey character was a bit different since Patsey did not experience any segregation treatment. This study concluded the portrayal of racial discrimination as shown in Solomon and Patsey characters occured as the result of white supremacy ideology as the basis thinking and belief of most white characters in the movie.